(untitled) (Bangladesh Journal of Urology, 2012)
Objective: To find out a method of percutaneous nephrolithotomy (PCNL) that can achieve greater stone clearance with acceptable morbidity. Patients and Methods: From January 2007 to May 2008, seventy patients were studied prospectively in two institutions and two other hospitals in Dhaka city for their complex renal stone management by percutaneous nephrolithotomy either with single tract or with multiple tract procedures. On the basis of assessment of calculus configuration and collecting system anatomy, patients who were managed with single tract PCNL labeled as Group A and those with multi-tract PCNL as Group B. Per-operative and post-operative events of all cases were analyzed for overall stone clearance, duration of operation time, per operative blood loss, post operative duration of haematuria, fever and analgesia requirement, urinary leakage through the nephrostomy tract, renal function and post operative hospital stay. Results: The mean stone size in Group A was 4.4(range 3.3- 6.9) cm and 5.8(range 4.1- 8.8) cm in Group B (p<0.05). Stone clearance in group A was 82.0 %( n=39) and in group B was 87.0 %(n=31).The mean operative time (min) of group A and B were 97.0+3.9 and 124.0+2.7 respectively(p<0.05). Mean blood loss was 347±18.7 ml and 424±42.7 ml with single and multiple tract group respectively (P<0.05). Blood transfusion needed in 25.8% patients of multiple tract group and 12.8% patients of single tract group (p>0.05). Among the postoperative outcomes, fever occurred in group A was 17.9 %( n=7) and in group B was 16.2 %( n=5). Analgesia requirement was higher in Group B (mean 187.50 ± 14.00 mg) than in Group A (mean 194.17 ± 15.71 mg) (p > 0.05). The mean haematuria (in days) occurred in group A was 1.97±0.93 and in group B was 2.23±0.92(p>0.05). Urine leakage stopped earlier in group-A (24.79 ± 4.15hours) than that in Group-B (26.73 ± 4.04 hours) (p>0.05). The mean serum creatinine (mg/dL) levels preoperatively was 1.14±0.40 and 1.58±0.98; postoperatively was 1.24±0.58 and 1.91±1.64 in group A and group B respectively (p<0.05). Mean hospital stay in days was 3.05± 0.17(range 7-2days) and 4.12 ± 0.15 (range 11-2days) in group A and group B respectively (p<0.05). During procedure, No conversion to open surgery was needed in either group. In two patients, one from each group, the procedure had to be deferred due to excessive bleeding and managed conservatively keeping nephrostomy tube followed by second look PCNL. Conclusion: Percutaneous nephrolithotomy with multiple tracts in a single session for treating complex stones in selected cases is safe, feasible and effective within acceptable morbidity in achieving a greater stone clearance. BJU 2010; 13(1): 21-33